Stressor, Social Support, Coping Strategy, Stress, and Life Satisfaction of Married Woman Student - Indrawati Zuhara; Istiqlaliyah Muflikhati; Diah Krisnatuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2017)
Stress can hinder academic success, especially for married women student because stress can decreased energy and motivation to do college activities and household tasks, therefore it is important for the students to avoid stress in order to have a good achievement at academic. This research aims to analyze the influence of individual characteristics, family characteristics, stressors, social support, coping strategies, and stress towards the married women students life satisfaction. The object of this research are post graduate women students of Bogor Agriculture University. Data collection is done using self-report method to 100 women married students. The collected data were analyzed using multiple linear regression test and corellation test. The most stressor came from itself, instrumental support was the most accepted among social support, most applied strategy in coping is the problem-focused strategy, the highest life satisfaction was life full of meaning and responsibility. Life satisfaction of married women students was influenced significantly positive by coping strategies and significantly negatif by stress.